2000
DOI: 10.1063/1.372017
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic analysis of the Si/SiO2 interface structure of thermally oxidized silicon

Abstract: The nature of the silicon oxide transition region in the vicinity of the Si/SiO2 interface is probed by infrared and x-ray photoelectron spectroscopies. The layer-by-layer composition of the interface is evaluated by uniformly thinning thermal oxide films from 31 Å down to 6 Å. We find that the thickness dependence of the frequencies of the transverse optical and longitudinal optical phonons of the oxide film cannot be reconciled by consideration of simple homogeneous processes such as image charge effects or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
206
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(233 citation statements)
references
References 27 publications
26
206
1
Order By: Relevance
“…Although there is only limited knowledge regarding the electrical properties of subnanometer SiO x layers, it was previously demonstrated that even for thermally grown SiO 2 layers, the initial 6 Å of the silicon oxide layer at the Si interface is predominantly substoichiometric. 21 This is supported by theoretical predictions showing a k value of 6-7 for a 6 Å interfacial substoichiometric SiO x layer between Si͑100͒ and 17 Å of SiO 2 . Our extracted median k value for sample A is 6.3, within the range of 6-7 predicted by theory.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Although there is only limited knowledge regarding the electrical properties of subnanometer SiO x layers, it was previously demonstrated that even for thermally grown SiO 2 layers, the initial 6 Å of the silicon oxide layer at the Si interface is predominantly substoichiometric. 21 This is supported by theoretical predictions showing a k value of 6-7 for a 6 Å interfacial substoichiometric SiO x layer between Si͑100͒ and 17 Å of SiO 2 . Our extracted median k value for sample A is 6.3, within the range of 6-7 predicted by theory.…”
Section: Resultssupporting
confidence: 68%
“…The method of extraction first assumes that the HRTEM images give accurate thickness estimates for all three samples ͓sample A: t͑SiO x ͒ =6 Å, t͑HfO 2 ͒ = 37 Å; sample B: t͑SiO x ͒ =19 Å, t͑HfO 2 ͒ = 37 Å; sample C: t͑SiO x ͒ =29 Å, t͑HfO 2 ͒ =40 Å͔. The second assumption is that the k value for the hafnium oxide layer falls within the range of [16][17][18][19][20][21][22][23][24][25]. The third assumption is that the k value for the IL is in the range of 3.9-8.0.…”
Section: Resultsmentioning
confidence: 99%
“…2. To the best of our knowledge, the band at $1300 cm À1 has never been observed on silica films and crystals [2,7,8,[23][24][25][26]. In addition, the band is by about 250 cm À1 higher than that of Si-O-Mo stretching vibrations on SiO 2 =Moð112Þ [2].…”
mentioning
confidence: 91%
“…Reduction of the TO−LO phonon energy splitting corresponds to the stress relaxation in a silicon oxide layer [11]. The increase in the splitting of TO−LO phonons is associated with stoichiometry growth at the silicon−silicon oxide interface as the SiO 2 content in the SiO/SiO 2 mixture increases [12].…”
Section: Macroporous Silicon Structures With Sio 2 Nanocoatingsmentioning
confidence: 99%